Islamic Religious Education as a Means of Fostering Moderate Religious Attitudes in Vocational High School Students - Talibo, Ishak; Sutrisno (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Learning Islamic Religious Education forms an attitude of religious moderation, which shows acceptance, openness, and synergy from different religious groups. This study aims to analyze the learning of Islamic Religious Education in forming an attitude of religious moderation and knowing the implications in students at Thoriqul Ulum Pacet Vocational School, Mojokerto Regency; this research uses qualitative research using case studies. For data collection, researchers used observation techniques, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, data validity, and conclusion drawing. The results of this study indicate that 1) PAI learning planning to realize religious moderation at Thoriqul Ulum Pacet Vocational School is very optimal in terms of a) the preparation of the syllabus and b) the development of lesson plans wherein the syllabus itself has been inserted (inserted) about religious moderation while in The lesson plan that uses the value of religious moderation is manifested both by learning methods or models and by adjusting material that contains religious moderation values. 2) Implications of PAI learning for realizing religious moderation, namely, students have excellent religious attitudes and social attitudes such as a) obey worship, b) respect others, c) establish familiarity, d) have social concern, and e) be tolerant.